Adaptive Solar Panel in Wiyata Tech Village, Towards Energy Independence - Wahid, Muhammad Rizalul; Zakaria, Diky; Abdulmajid, Nuur Wachid; Hamzah, Muhammad Bilal; Pamungkas, Agung Satria; Arlya, Zaky Khairul Fajar; Sembiring, Vladio Sada Arihta (Institut Teknologi Nasional, Bandung, 2025)
Nighttime illumination in Wiyata Tech Village, Kutamanah, Sukasari District, Purwakarta, has been limited due to the reliance on low-capacity lamps. To address this issue, solar panels were deployed to provide public street lighting (PSL), aiming to enhance energy autonomy and utilize renewable energy resources. The village, covering an area of 30.1 square kilometers, is part of Sukasari District, which spans 92.01 square kilometers and includes five villages. This community service project involved the installation of solar panels in Desa Kutamanah, with a participatory approach fostering local empowerment and technology adoption. A satisfaction survey conducted one month after installation revealed overwhelmingly positive feedback from residents, who noted significant improvements in lighting and community impact. The program successfully demonstrated the effectiveness of solar panels in improving street lighting, fostering energy independence, and encouraging sustainable use of renewable resources.